Pendidikan Kewarganegaraan dan Pendidikan Karakter Bangsa - Ananda, Azwar (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2012)
Civics concept is a doctrine fulfilled with relationship between citizens and state. The relation set a citizen as a member of political community. Civics education is needed to create good citizens whose have nation character. Nation character is needed for unified Indonesian which consist of various differentiation. This article analyze civics education, character education, beside strategy of teaching value in building the nation character. It becomes urgent because civics education had been focusing to cognitive aspects and gave less focuse to affective and psychomotoric sides. Key Words: Civics Education, Character Education, Nation Character